(3GdOQ GdefJNH aj JcedI JGQjN MdHs - (3bGVi GdbVGI YdGA GdOjf CHi GdMSf Ydj Hf eMeO Hf SYO Hf eMeO Hf Ydj GdWGFi GdMdHj GdTGaYj GdeYQha HGHf NWjH GdfGUQjIs; (3YeQ Hf CMeO Hf gHI Gddg Hf CHj LQGOI GdYbjdj, ceGd GdOjf GHf GdYOje,J (B660 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdCRdi , GdbOjQ GdCHOi s
(3BNQgG (B:s
(3jfJgi Edi BNQ JQLeI JZQi hQeT s
(3Ydi GdhQbI GdChd NW GdYdGeI GdSNGhi hGdbWH GdNjVQi hGdMSjf Hf YeQ GdfUjHi hYdi GdefLe GdQjGVi hGHf GdHGQRi hZjQges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B275s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B56 s
(3eUOQ GbJfGA GdCUd (B:s
(3dGdg di (B(2036) s
Keywords: (3GdJGQjNs